DIFFERENTIAL MODE MODELING OF PMSM FOR HIGH FREQUENCIES AND HARMONIC PULSES CALCULATION - Adam, Ali Ahmed; Gulez, Kayhan (WILEY-BLACKWELL, 2015)
This work proposes and analyses a model for a cable and permanent magnet synchronous motor to deal with high frequency differential mode components due to IGBT inverter systems. The model permits the study of the differential mode effects separately in the rotor reference frame. The experimental measurements show that the motor differential mode stray capacitances are functions of rotor position. The simulation results of the proposed differential mode circuits, together with the experimental results, show that the level of the differential mode noise currents is of significant value that cannot be ignored. The flow of some differential mode currents in the motor stator windings may contribute to torque pulsations which, require EMI noise filters to be used.
Keywords: Cable model; permanent magnet synchronous motor model; differential mode; rotor reference frame; EMI noise; high frequency model; DIRECT TORQUE CONTROL; LONG MOTOR LEADS; SYNCHRONOUS MOTOR; COMMON-MODE; INDUCTION-MOTORS; AC MOTORS; IDENTIFICATION; INVERTERS; MACHINES; DESIGN; Automation & Control Systems